Misoprostol and teratogenesis in neonates - Mariana Beatriz Scabora da Silva; Aline de Assis Ferreira; Soraya Ferreira Habr; Maria Martha Bernardi (Universidade de São Paulo, 2009)
This paper is focused in some aspects of maternal exposure to misoprostol during perinatal period, and the abortive and teratogenesis effects on the fetus. The causes of malformations were revised, taking into account chemical, physical and environmental factors as well as the interaction between them. There are evidences that the practice of abortion tripled in Southern and Northeastern Brazil in 15 years, and one of the most frequent forms of abortion is through the use of misoprostol. In Brazil, 1991, 288,700 women were hospitalized as a consequence of complications induced by abortion attempt with this medicine. This fact resulted in the ban of misoprostol across our country, by Decree 344/98 determined by the Health Ministry. The use of misoprostol requires special control and it is allowed only in hospitals, with supervision of the municipal health surveillance. Among the more severe problems affecting the non-aborted child is the injury on the central nervous system, which frequently results in the Moebius syndrome. This is a congenital and non-progressive paralysis of the VI and VII cranial nerves, frequently bilateral, which produces a unexpressive facial appearance and convergent Strabismus. Even banned in our country, abortion is illegally practiced, being deprived of proper knowledge about misoprostol teratogenic effects on the fetus as well as the risks involving mothers. Este trabalho enfoca aspectos relativos à exposição ao misoprostol no período perinatal como abortificante e agente teratogênico, assim como as causas das malformações, considerando-se fatores químicos, físicos e ambientais. A prática do aborto triplicou nas regiões Sul e Nordeste em 15 anos, sendo que entre os métodos mais freqüentes está o uso do medicamento com o princípio ativo do misoprostol. Em 1991 no Brasil, 288.700 mulheres foram socorridas em hospitais devido a complicações por indução de aborto com este medicamento. Isso resultou na proibição do misoprostol em todo país por determinação da portaria 344/98 do Ministério da Saúde, que exige um controle especial, onde sua utilização é permitida apenas em hospitais e com supervisão da vigilância sanitária municipal. Um dos problemas mais graves que a criança não abortada apresenta é uma injúria em seu sistema nervoso central desenvolvendo a Síndrome de Moebius. Esta é uma paralisia congênita e não progressiva do VI e do VII nervos cranianos, freqüentemente bilateral, que produz uma aparência facial pouco expressiva e estrabismo divergente. Neste sentido, mesmo sendo proibido em nosso país, o aborto induzido por misoprostol é praticado ilegalmente e sem uma verdadeira instrução da paciente sobre os efeitos teratogênicos do mesmo para ela e para seu bebê.